Case Report: Asuhan Keperawatan dengan Menerapkan Terapi Komunikasi Verbal Melalui Buku Saku “Suara AIUEO” pada Pasien Stroke - Kesuma Intani, Merlisa; Saputra, Dikki; Rumapea, Costan Tryono Parulian; Pratiwi, Nur Indah; Raharjo, Siti Rachmania Magister; Framita, Sisilia; Erja Natha Adit Pratama; Chindi Chenora (Journal of Community Development and Disaster Management, 2025)
Stroke is a non-communicable disease that commonly affects the elderly and can lead to verbal communication disorders, especially when it impacts the brain’s speech center. This study aims to determine the effectiveness of speech therapy using the “Suara AIUEO” pocket book in improving speech ability in patients with non-hemorrhagic stroke. The method used was a descriptive case study involving one patient who experienced motor aphasia due to stroke. The intervention was carried out by providing “AIUEO” speech therapy twice a day for three days, each session lasting 10–15 minutes. Speech ability was measured using the Derby Communication Scale, which includes aspects of expression, comprehension, and interaction. The results showed an improvement in the patient’s communication scores, particularly in expression and comprehension. The patient began to articulate vowels clearly and understand simple instructions. This therapy is not only effective but also simple, affordable, and can be performed by family members at home. With proper education, families can play a crucial role in the rehabilitation process. “AIUEO” therapy is recommended as part of a holistic nursing care approach for stroke patients with speech disorders.